Peningkatan Keterampilan Membaca Pemahaman dengan Menerapkan Model Reciprocal Teaching Siswa Sekolah Dasar - Anggraini, Sherly; Aprinawati, Iis; Ananda, Rizki; Pebriana, Putri Hana; Rizal, M. Syahrul (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This research is motivated by the low reading comprehension skills of students in Indonesian language lessons in grade V. This research aims to improve the reading comprehension skills of grade V UPT Elementary School 016 Bangkinang. The subjects used were 27 students consisting of 15 boys and 12 girls. The research method used was Classroom Action Research which was conducted in two cycles, each cycle consisting of two meetings. The data collection instrument was carried out using learning tools, observation sheets of teacher and student activities, and reading comprehension test questions. Data analysis techniques were carried out using qualitative and quantitative descriptions. Based on the results of data analysis, it can be seen that there is an increase in students' reading comprehension skills in the Indonesian language lesson content. Initial pre-action data of classical completeness was 44%, in cycle I meeting I decreased to 33%, cycle I meeting II increased to 63%, then in cycle II meeting I increased to 78%, and Cycle II meeting II increased to 85%. Thus, it can be concluded that the Reciprocal Teaching learning model can improve the reading comprehension skills of the fifth grade students of UPT SDN 016 Bangkinang.